Discussing health in high school: coronary artery disease (CAD) and its relation to gene, sedentary lifestyle and nutrition - Amaral, Cisnara Pires; Amaral, Eduarda Pires; de Borba , Luana Casarotto (Seven Editora, 2023)
The work in question is related to the "XXIII Scientific Exhibition" held in the School of Basic Education linked to the Integrated Regional University - URI where academics guided by the regent of the discipline of Biology stimulate high school students to perform scientific work that provides opportunities for research, scientific development and protagonism. The relevant points of the work are in the research and understanding carried out between the relationship of genetic and environmental factors and their actions in the development of Coronary Artery Disease (CAD); besides the perception regarding the learning opportunities of this work for high school students. To this end, a bibliographic research was conducted from the search of articles published between 2021 and 2022 found in the "PubMed" database, being discarded articles whose objective and results/conclusion were not consistent with the central idea of the work. Regarding the research it was concluded that genes are important factors for the possibility of the development of such diseases, however, a good diet and the practice of physical exercises appear as limiting factors for CAD to manifest, considering their influence on the body, because it is proven that genes contribute very little to the action of coronary heart disease. In relation to the student’s protagonism, it was observed that the research provided scientific knowledge, the opportunity to dialogue with scholars, and the incentive to research, understanding that it is an essential factor for the development of criticality, autonomy, competence, and learning in a significant way. DOI: https://doi.org/10.56238/colleinternhealthscienv1-006